Reduplikasi Bahasa Melayu Riau Dialek Rokan Hulu - Lismarni '; Mangatur Sinaga; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study titled is Reduplication of Riau Malay dialect Rokan Hulu. This study aims to describe the type of reduplication Riau Malay dialect Rokan Hulu and explain the meaning contained in the dialect of the Malay language Reduplication Rokan Hulu. The method used in this research is descriptive research. Based on geographical data, the author determin saurce of data fromrepreseninformants everings districts . Every village of the total districts represented by two informants so that the number of informants study is 18 peoples. The result of this resul have onstained: (1) thetypes of dwipurwa reduplication with affixes there are eleven of datas,(2)dwilingga reduplication there areseventh of datas, (3) dwilingga reduplication phoneme exchange there are three datas, (4) konfiks reduplicationthere are four datas, (5) prefixed reduplication with the phallus first lingga there were nine of datas, (6) prefixed reduplication with the second lingga there are fivedatas, (7) suffixes reduplication there arethree datas (8) Infix reduplication there are three datas,(9) simulfix reduplicationthere are seven datas, (10) the meaning ofdwipurwa reduplications with affixes (sake, many times / repeatable and highly / intensity) there are trhee datas, (11) meaning ofplural dwilingga reduplications there is one data, (12) the meaning ofsound copy dwilingga (mutual / reverb) thereis one of datas, (13) the meaning of konfiks reduplications (many / plural) the is one data, (14) prefixing reduplications on the firts lingga (many / plural, intensity / very / more , casually, superlative / most, and up / ever) there are five of datas, (15) prefixed reduplication on the second linggareplay / each) there are two datas, (16) suffix reduplication (many / plural) there is one of data, (17) infix reduplication (are taking place / continuous) there is one of data, (18) simulfix reduplications (most / superlative, replay / each other, and many times) there are three of datas.Keywords : types and reduplication ofmeaning contained in Rokan Hulu .